Γ-Aminobutyric Acid (GABA) Concentration Inversely Correlates with Basal Perfusion in Human Occipital Lobe. Issue 3 (March 2014) - Donahue, Manus J; Rane, Swati; Hussey, Erin; Mason, Emily; Pradhan, Subechhya; Waddell, Kevin W; Ally, Brandon A
Commonly used neuroimaging approaches in humans exploit hemodynamic or metabolic indicators of brain function. However, fundamental gaps remain in our ability to relate such hemo-metabolic reactivity to neurotransmission, with recent reports providing paradoxical information regarding the relationship among basal perfusion, functional imaging contrast, and neurotransmission in awake humans. Here, sequential magnetic resonance spectroscopy (MRS) measurements of the primary inhibitory neurotransmitter, γ -aminobutyric acid (GABA+macromolecules normalized by the complex N-acetyl aspartate- N -acetyl aspartyl glutamic acid: [GABA + ]/[NAA–NAAG]), and magnetic resonance imaging (MRI) measurements of perfusion, fractional gray-matter volume, and arterial arrival time (AAT) are recorded in human visual cortex from a controlled cohort of young adult male volunteers with neurocognitive battery-confirmed comparable cognitive capacity (3 T; n =16; age=23±3 years). Regression analyses reveal an inverse correlation between [GABA + ]/[NAA–NAAG] and perfusion ( R =−0.46; P =0.037), yet no relationship between AAT and [GABA + ]/[NAA–NAAG] ( R =−0.12; P =0.33). Perfusion measurements that do not control for AAT variations reveal reduced correlations between [GABA + ]/[NAA–NAAG] and perfusion ( R =−0.13; P =0.32). These findings largely reconcile contradictory reports between perfusion and inhibitory tone, and underscore the physiologic origins of the growing literature relating functional imaging signals, hemodynamics, and neurotransmission.